2013
DOI: 10.3111/13696998.2013.778268
|View full text |Cite
|
Sign up to set email alerts
|

The cost burden of multiple sclerosis in the United States: a systematic review of the literature

Abstract: MS is a costly chronic disease. Further research is needed to understand: costs by MS type, costs associated with increasing disability and early retirement, and the potential impact of new treatments expected to launch in coming years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
137
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(140 citation statements)
references
References 36 publications
2
137
1
Order By: Relevance
“…1 The Department of Veterans Affairs (VA) health-care system treats approximately 16,000 veterans with MS each year. 2 MS is a chronic disease that results in an annual cost burden of $8500 to $54,000 per patient in the United States, much of it from complications secondary to MS. 3,4 Two recent studies have demonstrated an increased risk of infection-related hospitalizations and infectionrelated mortality in patients with MS compared with those without MS in Sweden and the United Kingdom. 5,6 The objective of this study was to examine the risk of hospitalization and death due to infections in patients with and without MS in a cohort of US veterans.…”
mentioning
confidence: 99%
“…1 The Department of Veterans Affairs (VA) health-care system treats approximately 16,000 veterans with MS each year. 2 MS is a chronic disease that results in an annual cost burden of $8500 to $54,000 per patient in the United States, much of it from complications secondary to MS. 3,4 Two recent studies have demonstrated an increased risk of infection-related hospitalizations and infectionrelated mortality in patients with MS compared with those without MS in Sweden and the United Kingdom. 5,6 The objective of this study was to examine the risk of hospitalization and death due to infections in patients with and without MS in a cohort of US veterans.…”
mentioning
confidence: 99%
“…The financial burden accompanying MS is a central component of the disease experience, ranking second among all chronic conditions in direct costs behind congestive heart failure [3]. In addition to the impact of decreased productivity and unemployment [4][5][6], patients often shoulder the burden of high outof-pocket costs for medications, tests, MRIs, medical equipment, and inpatient/outpatient visits [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies examining interactions beyond HLA, such as the >110 non-MHC MS genetic variants 3 and obesity remain to be investigated, as do interactions between obesity and other established environmental factors, such as smoking and vitamin D level.…”
Section: Genetic and Environmental Interactionsmentioning
confidence: 99%
“…It is characterized by the presence of inflammation, neurodegeneration, and demyelinating lesions of white and gray matter. Health care costs in the U.S. associated with MS range from $8,500 to upwards of $52,000 per patient year 3 . Both genetic and environmental factors have been implicated in MS etiology.…”
Section: Introductionmentioning
confidence: 99%